Tourism Branding Strategy In The Era Of The Covid-19 Pandemic (Sebangkong Valley Swimming Pool Tour, Tempursari Village Candimulyo Magelang) - Safitri, Hikmawati Fajri Devi; Sari, Yoana Puspita (Prosiding University Research Colloquium, 2021)
Tourism is one of the sectors affected by the COVID-19 pandemic. The Sebangkong ValleySwimming Pool Tour is one of the regional tours under the Village Owned Enterprise(BUMDES) which is also affected by the pandemic. Several problems that continue to arisewithout resolution have resulted in this tour having to be closed for an undetermined timelimit. The method used by the researcher is interviews, observation and documentation.Interviews were conducted in-depth with open-ended questions. Observations were madethrough direct (field) observations and observations of digital media such as websites andInstagram. From the results obtained, it can be concluded that the manager of theSebangkong Valley Swimming Pool for conducting tourism in the pandemic era requireslearning or training related to understanding village tourism, approaches anddevelopment of community-based tourism (CBT), strengthening management of villagetourism managers or human resources, briefing and formation of awareness groups.tourism (Pokdarwis), utilization of the allocation of funds to build village tourism, anddigital tourism promotion training with social media.